Improvement of natural grassland as a factor of rural development in lower Danube Region - Marijana Jovanović; Slavica Arsić; uro Pajčin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The aim of this paper is presenting of importance of natural grasslands (meadows and pastures) in rural development of Lower Danube region. Production of efficient quantities of food for domestic animals and preservation of environment is strategically important for economic prosperity and animation of local population, as an aim to stay in rural areas and to develop their agricultural productivity. Lower Danube region have possibilities for development of agricultural production, because it possessed enough quantity of natural resources with highest quality. The territory of Lower Danube region make following municipalities: Golubac, Majdanpek, Negotin, Kladovo and Kuécevo. In this municipalities land under meadows and pastures is on the second place, just behind arable land. Due to the presence of NP erdap on the territory of Lower Danube region is concluded that there are no obstacles for rural development, from the aspect of natural resources. But the following problems: fragmentation of land, the extensiveness of use, inadequate intake of organic matter and degradation processes caused by the action of man, affectedthe quality of natural grassland (meadows and pasture) and the production of forage crops in general. Because of that one of the most important tasks of rural development of these municipalities is proper using of grassland, which going to enabled development of this kind of agricultural production and protection of important plant.
Keywords: 330; pastures; meadows; rural development; Lower Danube Region